Analyzing the implementation of K13 and Kurikulum Merdeka: Students’ perceptions - Shofwatut Tarbiyah; Fitria Zulaika Mahfudza; Nizma Amelia Putri; Diah Kusuma Ningrum; Yumnaa Taqiyatul Nabillah (Universitas Pendidikan Indonesia, 2025)
The development of the times must always be followed, demanding the formation of the Kurikulum Merdeka, which is expected to prepare students better to keep up with global developments compared to the 2013 Curriculum (K13). This study aims to analyze the implementation of K13 and Kurikulum Merdeka according to student perceptions. A quantitative method with a descriptive approach was used in this study, which involved 41 respondents. The questionnaire includes ten statements related to implementing K13 and Kurikulum Merdeka. The results of the questionnaire are depicted in the form of pie charts. This research shows students' preferences. K13 is superior in final assessment regarding the amount of learning and easy-to-understand material. Meanwhile, Kurikulum Merdeka has higher ratings regarding flexible learning time, active learning, fun teaching methods, and complex material. Students preferred both creative learning and how this curriculum implements projects. The transition readiness from K13 to Kurikulum Merdeka is equal between those who agree and those who are neutral. Abstrak Perkembangan zaman harus selalu diikuti menuntut pembentukan Kurikulum Merdeka yang diharapkan dapat lebih mempersiapkan peserta didik untuk mengikuti perkembangan global dibandingkan Kurikulum 2013 (K13). Penelitian ini bertujuan untuk menganalisis implementasi K13 dan Kurikulum Merdeka menurut persepsi peserta didik. Metode kuantitatif dengan pendekatan deskriptif digunakan dalam penelitian ini melibatkan 41 responden. Kuesioner mencakup sepuluh pernyataan yang berkaitan dengan implementasi K13 dan Kurikulum Merdeka. Hasil kuesioner digambarkan dalam bentuk diagram lingkaran. Penelitian ini menunjukkan preferensi peserta didik. K13 lebih unggul dalam bidang penilaian akhir, jumlah materi pembelajaran dan materi yang mudah dipahami. Sementara itu, Kurikulum Merdeka memiliki peringkat yang lebih tinggi dalam hal waktu belajar yang fleksibel, pembelajaran aktif, metode pengajaran yang menyenangkan, dan materi yang rumit. Untuk pembelajaran kreatif, peserta didik lebih menyukai keduanya, begitu juga dengan bagaimana kurikulum ini mengimplementasikan proyek. Hasil dari kesiapan transisi dari K13 ke Kurikulum Merdeka adalah sama antara yang setuju dan netral. Kata Kunci: implementasi kurikulum; K13; Kurikulum Merdeka